2008
DOI: 10.1001/archinternmed.2007.66
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes by Race in Hypertensive Patients With and Without the Metabolic Syndrome<subtitle>Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT)</subtitle>

Abstract: The ALLHAT findings fail to support the preference for calcium channel blockers, alpha-blockers, or angiotensin-converting enzyme inhibitors compared with thiazide-type diuretics in patients with the MetS, despite their more favorable metabolic profiles. This was particularly true for black participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 33 publications
1
60
0
1
Order By: Relevance
“…All-cause mortality was significantly lower in smokers encouraged to discontinue smoking as compared to control group not receiving aggressive and program-specific instructions. Thus, it was concluded that even modest level participation in smoking cessation provided important mortality reduction benefit [138]. Cigarette smoking exacerbates the already elevated risk of death in patients with CMS [139].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…All-cause mortality was significantly lower in smokers encouraged to discontinue smoking as compared to control group not receiving aggressive and program-specific instructions. Thus, it was concluded that even modest level participation in smoking cessation provided important mortality reduction benefit [138]. Cigarette smoking exacerbates the already elevated risk of death in patients with CMS [139].…”
Section: Smoking Cessationmentioning
confidence: 99%
“…16 Activation of the renin-angiotensin system (RAS) is the major cause of hypertension because stimulation of the angiotensin II receptor increases oxidative stress, causes endothelial dysfunction, and promotes atherosclerosis. 17 Activation of the RAS has also been associated with abnormal secretion of cytokines in adipose cells.…”
Section: Metsmentioning
confidence: 99%
“…Thiazide diuretics also may have dyslipidemic and diabetogenic effects when used at high doses, although this has been questioned by the findings of the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack trial that failed to support the preference for calcium channel blockers, ␣-blockers, or angiotensin-converting enzyme inhibitors compared with thiazide-type diuretics in patients with metabolic syndrome. 37 The AHA/ASA guideline recommends consideration of a diuretic in combination with an angiotensin-converting enzyme inhibitor. 35 Table 3 lists recommendations for BP management according to AHA/ASA guidelines.…”
Section: Questions and Answers About Bp Management For Recurrent Stromentioning
confidence: 99%